Application of Calixarene as A Phase Transfer Catalyst in Vanilin Synthesis from Eugenol - Suryadi Budi Utomo; Tresni Setiati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
This study aims to synthesize the compound of C-2,8,14,20-tetradodecylcalix[4]arene-4,6,10,12,16,18,22,14-octol and test it as a phase transfer catalyst. The calixarene compound was prepared by reacting 1,3-dihydroxybenzene with dodecanal under acid-catalyzed. The desired calixarene was then tested for its ability as a phase transfer catalyst for oxidation of isoeugenol with KMnO4 to obtain vanillin products. The results showed that C-2,8,14,20-tetradodecylcalix[4]arene-4,6,10,12,16,18,22,14-octol can be synthesized from 1,3-dihydroxybenzene with a yield of 89.5%. The compound able to work as a phase transfer catalyst which is marked by the oxidation of isoeugenol to produce as much as 12.15% of vanillin. The vanillin product obtained was analyzed by an IR spectrometer that indicating the presence of the most important group namely aldehyde. The results of the analysis with the H-NMR spectrometer showed absorption at 3.9 ppm chemical shift with singlet appearance i.e. protons from –OCH3 (methoxy), uptake in chemical shifts 7.0 and 7.4 ppm with multiplet appearance i.e. protons from aromatic rings, uptake in chemical shifts of 9.8 ppm with singlet appearance i.e. protons from –CHO (aldehyde).